2019
DOI: 10.15280/jlm.2019.9.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Intervention for Breast Cancer Women

Abstract: Breast cancer patients have various physical, psychological health risks, among which are the effects on general health. Lifestyle intervention involving nutrition education, physical activity, and stress management, and has been shown to be effective in improving the health of breast cancer patients. Therefore, it is necessary to develop and apply a lifestyle intervention program to promote health in breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Since the leading risk factor for developing breast cancer stems from prolonged exposure to endogenous hormones, it is not easily modifiable. 51 Primary prevention of breast cancer is achieved by partaking in physical activity, maintaining a healthy weight, following a healthy diet, minimizing alcohol consumption, breastfeeding children, and minimizing the use of oral contraceptive pills and hormone replacement therapy. 51 Testing for BRCA1 and BRCA2 mutations is recommended in women with affected family members.…”
Section: Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the leading risk factor for developing breast cancer stems from prolonged exposure to endogenous hormones, it is not easily modifiable. 51 Primary prevention of breast cancer is achieved by partaking in physical activity, maintaining a healthy weight, following a healthy diet, minimizing alcohol consumption, breastfeeding children, and minimizing the use of oral contraceptive pills and hormone replacement therapy. 51 Testing for BRCA1 and BRCA2 mutations is recommended in women with affected family members.…”
Section: Preventionmentioning
confidence: 99%
“…51 Primary prevention of breast cancer is achieved by partaking in physical activity, maintaining a healthy weight, following a healthy diet, minimizing alcohol consumption, breastfeeding children, and minimizing the use of oral contraceptive pills and hormone replacement therapy. 51 Testing for BRCA1 and BRCA2 mutations is recommended in women with affected family members. 52 A bilateral mastectomy may be performed as prophylaxis for women who test positive for the mutations which are associated with increased risk of breast cancer.…”
Section: Preventionmentioning
confidence: 99%
“…The incidence of breast cancer is increasing rapidly [1]. Of all cancers in women, breast cancer has the highest incidence rate and highest mortality rate [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we found in a screening test that the MeOH extract of L. cuneata exerted inhibitory effect on metabolic activity in MCF-7 human breast cancer cells, which led us to perform further phytochemical analysis and identify the bioactive compound(s) responsible for these effects. Bioassay-guided fractionation and chemical investigation of the MeOH extract led to the isolation of nine compounds (four lignan glycosides (1)(2)(3)(4), three flavonoid glycosides (5)(6)(7), and two phenolic compounds (8 and 9)). The structures of the isolated compounds were identified by LC-MS analysis and their spectroscopic data and physical data were compared with previously reported values.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is 1 of the most common cancers diagnosed in females around the world. [13] In addition, it is a heterogeneous disease with a variety of subtypes between and within tumors. [46] The 3 major subtypes of comprehensive gene expression comprise of luminal, human epidermal growth factor receptor 2 (HER2)-positive, and basal-like cancers.…”
Section: Introductionmentioning
confidence: 99%